The Influence of Acute Stress on Brain Dynamics - Lin, Chin-Teng; Wang, Yu-Kai; Fan, Jhe-Wei; Chen, Shi-An (My University, 2013)
Living under high stress may be unhealthy. This study explores electroencephalography (EEG) correlated with stressful circumstances by using the task-switching paradigm with feedback information. According to the behavioral and physiological evidence, acute stress created by this paradigm affected the performance of participants. Under stress, the participants responded quickly and inaccurately. The EEG results correlated with acute stress were found in the frontal midline cortex, especially on the theta and alpha bands. These specific factors are considered importance features for detecting the influence of stress by applying various machine-learning methods and neuro-fuzzy systems. This comprehensive study can provide knowledge for studying stress and designing Brain-Computer Interface (BCI) systems in the future.
Keywords: EEG; Task Switching; Stress; Neuro-Fuzzy System; Brain-Computer Interface (BCI)